2006
DOI: 10.1038/ng1810
|View full text |Cite
|
Sign up to set email alerts
|

A mutation creating a potential illegitimate microRNA target site in the myostatin gene affects muscularity in sheep

Abstract: Texel sheep are renowned for their exceptional meatiness. To identify the genes underlying this economically important feature, we performed a whole-genome scan in a Romanov x Texel F2 population. We mapped a quantitative trait locus with a major effect on muscle mass to chromosome 2 and subsequently fine-mapped it to a chromosome interval encompassing the myostatin (GDF8) gene. We herein demonstrate that the GDF8 allele of Texel sheep is characterized by a G to A transition in the 3' UTR that creates a target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
859
1
16

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,152 publications
(917 citation statements)
references
References 18 publications
23
859
1
16
Order By: Relevance
“…1 However, the focus is principally on finding genetic association with common SNPs located in miR genes or miR-binding target sites, 2 and very few studies aimed to identify rarer variants in case-control series even if large scale resequencing approaches focusing on miR genes and 3ʹ-UTR are starting to be used. 3 This paucity of mutation screening studies could stem from the difficulty in interpreting rare variants that would be identified by such an approach, miR true targets remaining rather scarce, their genes poorly characterized, not to mention their regulation.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, the focus is principally on finding genetic association with common SNPs located in miR genes or miR-binding target sites, 2 and very few studies aimed to identify rarer variants in case-control series even if large scale resequencing approaches focusing on miR genes and 3ʹ-UTR are starting to be used. 3 This paucity of mutation screening studies could stem from the difficulty in interpreting rare variants that would be identified by such an approach, miR true targets remaining rather scarce, their genes poorly characterized, not to mention their regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Deletions or mutations in the GDF8 gene can cause an increase in skeletal muscle mass as a result of both muscle hypertrophy and hyperplasia in a number of animal species including sheep (Clop et al, 2006), cattle (Gill et al, 2009;Kambadur et al, 1997) and dog (Mosher et al, 2007). GDF11 also appears to play a crucial role in skeletal development, as knock-out mice display skeletal defects resulting from abnormal anterior-posterior patterning (McPherron et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In Texel sheep, the myostatin allele characterized by a G to A mutation in myostatin 3'UTR creates a target site for miR-1 and miR-206 (Clop et al, 2006). High expression of miR-1/ 206 in muscle inhibits transcript level of myostatin, which contributes to muscular hypertrophy (Clop et al, 2006).…”
Section: Discussionmentioning
confidence: 99%